A Unified Controller for Multi-State Operation of the Bi-Directional Buck–Boost DC-DC Converter - Gabriel R. Broday; Gilney Damm; William Pasillas-Lépine; Luiz A. C. Lopes (Energies, 2021)
DC grid interfaces for supercapacitors (SCs) are expected to operate with a wide range of input voltages with fast dynamics. The class-C DC-DC converter is commonly used in this application because of its simplicity. However, it does not work if the output voltage (V2) becomes smaller than the input voltage (V1). The non-isolated bi-directional Buck–Boost DC-DC converter does not have this limitation. Its two half-bridges provide a means for controlling the power flow operating in the conventional dual-state mode, as well as multi-state, tri, and quad modes. These can be used for mitigating issues such as the Right Half Plane (RHP) zero that has a negative impact on the dynamic response of the system. Multi-state operation typically requires multi-variable control, which is not easy to realize with conventional PI-type controllers. This paper proposes a unified controller for multi-state operation. It employs a carrier-based modulation scheme with three modulation signals that allows the converter to operate in all four possible states and eight different modes of operation. A mathematical model is developed for devising a multi-variable control scheme using feedback linearization. This allows the design of control loops with simple PI controllers that can be used for all multi-state modes under a wide range of operating conditions with the same performance. The proposed scheme is verified by means of simulations.